Echium amoenum L. Ethanol Extract Protects Retinal Ganglion Cell after Glutamate and Optic Nerve Crush Injury. (22nd September 2022) - Li, Haibo; Behnammanesh, Ghazaleh; Wu, Zhenkai; Rong, Rong; You, Mengling; Majid, Aman Shah Abdul; Ji, Dan
Abstract : The development of low-cost and effective natural products for treating neuron degenerative diseases have proven to be safe and potentially effective. Echium amoenum L. (Boraginaceae) is an annual herb that grows wildly in Europe and western Asia. The aim of this study was to evaluate the neuroprotective properties of an ethanol extract of E. amoenum L. The effects of E. amoenum L. extract on oxidative stress were measured in the rat R28 retinal precursor cell line. Furthermore, the protective role of the extract on the glutamate-induced and optic nerve crush (ONC) injury-induced cell death were evaluated in vitro and in vivo, respectively. Our results showed that the ethanol extract of E. amoenum L. prevented the glutamate-induced decrease in cell viability and increase in cell death in R28 cells and suppressed the overproduction of ROS induced by glutamate. Moreover, the extract significantly inhibited microglial activation and optic nerve damage induced by ONC injury in mice. In addition, the mechanism was attributed to the ability of the extract to decrease NF- κ B pathway activation and its downstream inflammatory cytokine production. In conclusion, E. amoenum L. ethanol extract had a potent neuroprotective effect against glutamate-induced and ONC-induced cell death. This is likely due to its antioxidant and anti-inflammatory properties.